Stratigraphic architecture of Solander Basin records Southern Ocean currents and subduction initiation beneath southwest New Zealand. (3rd June 2020) - Patel, Jiten; Sutherland, Rupert; Gurnis, Michael; Van Avendonk, Harm; Gulick, Sean P. S.; Shuck, Brandon; Stock, Joann; Hightower, Erin
Abstract: Solander Basin is characterized by subduction initiation at the Pacific‐Australia plate boundary, where high biological productivity is found at the northern edge of the Antarctic Circumpolar Current. Sedimentary architecture results from tectonic influences on accommodation space, sediment supply and ocean currents (via physiography); and climate influence on ocean currents and biological productivity. We present the first seismic‐stratigraphic analysis of Solander Basin based on high‐fold seismic‐reflection data (voyage MGL1803, SISIE). Solander Trough physiography formed by Eocene rifting, but basinal strata are mostly younger than ca. 17 Ma, when we infer Puysegur Ridge formed and sheltered Solander Basin from bottom currents, and mountain growth onshore increased sediment supply. Initial inversion on the Tauru Fault started at ca. 15 Ma, but reverse faulting from 12 to ca. 8 Ma on both the Tauru and Parara Faults was likely associated with reorganization and formation of the subduction thrust. The new seabed topography forced sediment pathways to become channelized at low points or antecedent gorges. Since 5 Ma, southern Puysegur Ridge and Fiordland mountains spread out towards the east and Solander Anticline grew in response to ongoing subduction and growth of a slab. Solander Basin had high sedimentation rates because (1) it is sheltered from bottom currents by Puysegur Ridge; and (2) it has a mountainous land area that supplies sediment to its northern end. Sedimentary architecture is asymmetric due to the Subtropical Front, which moves pelagic and hemi‐pelagic sediment, including dilute parts of gravity flows, eastward and accretes contourites to the shelf south of Stewart Island. Levees, scours, drifts and ridges of folded sediment characterize western Solander Basin, whereas hemi‐pelagic drape and secondary gravity flows are found east of the meandering axial Solander Channel. The high‐resolution record of climate and tectonics that Solander Basin contains may yield excellent sites for future scientific ocean drilling. Abstract : Depositional patterns in Solander Basin are caused by the interplay between sediment gravity flows sourced from tectonically‐active mountains, pelagic biogenic sediment, and the Subtropical Front, which is a strong ocean current that modifies deposition. Tectonic growth of Puysegur Trench and Ridge since ~17 Ma created an oceanographic barrier and hence depocentre. Ongoing growth of secondary faults since then has changed sediment supply and pathways, and can be linked to progressive maturity of subduction initiation.